Analisis Implementasi Pendidikan Multikultural di Sekolah - Muhanna, Hafiz Attha; Paramita Sari, Gilang Jathi; Fauziyyah, Alifa Nida; Anindya, Putri Rahma (TSAQOFAH, 2022)
Indonesian people, especially students, must be able to be aware of and understand multiculturalism from an early age. By understanding the multiculturalism of the Indonesian people, especially students, they can appreciate the differences that exist in Indonesia, such as religious differences, language differences, gender differences, and ethnic differences. Therefore, the role of the teacher is very important and very large to instill multicultural education to students from an early age so that students can respect the differences of other cultures and can apply cultural values ​​in everyday life. In addition, the role of the teacher here must also master various methods and concepts of learning so that students can receive learning well in addition to the differences that exist. With this multicultural education learning, students are able to be critical and active in respecting and dealing with all these differences. In learning, the most important thing is to apply multicultural education so that students can get used to being tolerant and respectful of others in the surrounding environment.